Tinjauan Persiapan Sertifikasi Halal di Industri Farmasi : Studi Kasus Analisis Titik Kritis Kehalalan Bahan Aktif dan Eksipien - Priskila Margaretha; Nyi Mekar Saptarini (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Indonesia, as the country with the largest Muslim population in the world, has a significant demand for halal products, including pharmaceuticals. Halal certification serves not only as a regulatory compliance requirement but also as a strategic tool to build consumer trust, ensuring that products meet both religious and quality standards. This article aims to descriptively examine the process and challenges of preparing for halal certification in the pharmaceutical industry, focusing on the evaluation of active pharmaceutical ingredients (APIs) and excipients. The study is based on firsthand experience during a pharmacist professional practice (PKPA) at a national pharmaceutical company. Key areas of focus include material flowchart analysis, identification of critical non-halal points, and the implementation of the Halal Product Assurance System SJPH, in line with Indonesian halal regulatory frameworks. The findings highlight the importance of systematically identifying critical points, especially in evaluating the origin and status of materials such as alcohol, enzymes, and activated carbon, which frequently raise concerns in halal compliance. Furthermore, successful implementation requires comprehensive documentation, revision of standard operating procedures (SOPs), and staff training to ensure traceability and consistency throughout the supply chain. Collaboration with the Indonesian Ulema Council (MUI) and the Halal Product Assurance Organizing Agency (BPJPH) is also vital for technical guidance and certification processes. The study concludes that a structured and integrated approach to halal assurance not only facilitates certification but also enhances operational quality and market competitiveness. This study is expected to provide practical insights for pharmaceutical industries in effectively and sustainably implementing halal regulations, contributing to broader consumer protection and industry accountability.